Nitrogen Type and Availability Drive Mycorrhizal Effects on Wheat Performance, Nitrogen Uptake and Recovery, and Production Sustainability - Ingraffia, Rosolino; Amato, Gaetano; Sosa-Hernández, Moisés A.; Frenda, Alfonso S.; Rillig, Matthias C.; Giambalvo, Dario (Frontiers in Plant Science, 2020)
Plant performance is strongly dependent on nitrogen (N), and thus increasing N nutrition is of great relevance for the productivity of agroecosystems. The effects of arbuscular mycorrhizal (AM) fungi on plant N acquisition are debated because contradictory results have been reported. Using 15N-labeled fertilizers as a tracer, we evaluated the effects of AM fungi on N uptake and recovery from mineral or organic sources in durum wheat. Under sufficient N availability, AM fungi had no effects on plant biomass but increased N concentrations in plant tissue, plant N uptake, and total N recovered from the fertilizer. In N-deficient soil, AM fungi led to decreased aboveground biomass, which suggests that plants and AM fungi may have competed for N. When the organic source had a low carbon-to-nitrogen ratio, AM fungi favored both plant N uptake and N recovery. In contrast, when the organic source had a high carbon-to-nitrogen ratio, a clear reduction in N recovery from the fertilizer was observed. Overall, the results indicate an active role of arbuscular mycorrhizae in favoring plant N-related traits when N is not a limiting factor and show that these fungi help in N recovery from the fertilizer. These results hold great potential for increasing the sustainability of durum wheat production.